Values of Metabolizable Energy and Metabolization of Nutrients for Slow- and Fast-growing Birds at Different Ages - FR Santos (Revista Brasileira de Ciência Avícola, 2015)
Two trials were performed to determine apparent metabolizable energy (AME) and AME corrected for zero nitrogen balance (AMEn) values and coefficients of apparent metabolizability of nitrogen (CAMN) and of ether extract (CAMEE) of slow- and fast-growing broilers (Isa label and Cobb, respectively) fed four different diets between 10 to 17 days or 28 to 35 days of age. The method of total excreta collection was applied. The tested feedstuffs were corn, whole corn germ (WCG), sorghum, and soybean meal (SBM). A randomized block experimental design was applied, with two treatments (breeds) and four replicates of ten animals each in the first trial, and four replicates of six animals each in the second trial. No differences in CAMN values were observed between the breeds; however, Isa Label birds presented higher CAMEE for all tested feedstuffs. The AME and AMEn values obtained in Isa Label chickens fed the corn diet were 5.75 and 3.44% higher relative tothe Cobb birds, respectively. Breed did not influence AME and AMEn values of the other tested feedstuffs. Independently of breed, age influenced the AME and AMEn values of WCG, sorghum and SBM, suggesting that birds become utilize feed more efficiently as they age.